Serum miR-365b-5p/miR-222-5p as a potential diagnostic biomarker for long-term weight loss in patients with morbid obesity after bariatric surgery - Mela-Rivas, Virginia; Martín-Reyes, Flores; Oliva-Olivera, Wilfredo; Cantarero-Cuenca, Antonio; Sánchez-García, Ana; Sancho-Marín, Raquel; González-Jiménez, Andrés; Tomé, Mónica; Moreno-Ruiz, Francisco Javier; Soler Humanes, Rocío; Fernández-Serrano, José Luis; Sánchez-Gallegos, María Pilar; et al. (Elsevier, 2025)
There is a strong association between obesity and adverse health outcomes [1]. A number of conservative therapies have demonstrated limited efficacy with regard to weight loss and the management of comorbidities. Bariatric surgery has been regarded as the most efficacious therapeutic approach for severe obesity, as it induces weight loss and modifies metabolism to control morbid obesity and systemic comorbidities [2]. However, there are some discrepancies about it in the literature since 5-20% of the patients do not achieve a successful long-term weight loss [3,4]. Therefore, the identification of biomarkers associated with successful weight loss following bariatric surgery would facilitate the development of personalized medicine, as well as enable the integration of additional interventions in cases where adequate weight loss is not anticipated. However, the specific biomarkers that can predict surgical outcomes remain unclear, representing a crucial step in the advancement of personalized medicine.

In recent years, significant research has been conducted with the aim of identifying genes associated with obesity. This research has sought to enhance our understanding of the underlying mechanisms, identify new targets for clinical therapy, and facilitate the early prediction of metabolic complications and treatment response. Indeed, there is an accumulating body of evidence that epigenetic regulation of gene expression represents a significant contributor to the variation in predisposition to obesity and associated comorbidities [5]. In this context, miRNAs have been demonstrated to regulate a multitude of cellular processes at the post-transcriptional level, including cell growth, proliferation, differentiation, DNA repair, and apoptosis [6]. Deregulation of miRNA profiles has been associated with a number of pathological conditions [7-9]. Furthermore, miRNAs have been identified as a key regulator of various biological processes associated with obesity, including inflammation, adipogenesis, adipocyte differentiation, metabolic integration, fat metabolism, and insulin sensitivity [10-11]. Although miRNAs act at the subcellular level, they can also be found in the circulatory system. The biological implications and physiological role of circulating miRNAs remain unclear, despite their potential involvement in intercellular communication. Consequently, these miRNAs have gained clinical and therapeutic relevance as novel biomarkers, with changes in their profile indicating the presence of physio-pathological conditions [12].

A number of studies have indicated that specific stimuli can influence the miRNA profile of patients, thereby promoting health improvement. The intake of macronutrients, the composition of energy-restricted diets with varying carbohydrate and fat ratios, and the physical condition of the individual all influence the pattern of circulating miRNAs [13- 14]. In the context of bariatric surgery, some studies have demonstrated alterations in postoperative circulating miRNA expression, which have been associated with an improvement in the metabolic state of patients [15]. However, given the genetic background of obesity, it is reasonable to hypothesize that predictors may be identified within the genetic context. Therefore, the present study aims to determine whether the circulating miRNA profile can be used as a predictive biomarker for the success of a bariatric surgery in patients with morbid obesity.
https://openpolicyfinder.jisc.ac.uk/id/publication/4794
Keywords: Obesidad - Cirugía; Obesidad mórbida; Adelgazamiento; Marcadores bioquímicos; Bariatric surgery; Morbid obesity; Percentage of excess weight loss; miR-222-5p; miR-365b-5p; miRNA